Ailesel Hipokalemik Periyodik Paralizi - Olgu Sunumu - (:unkn) unknown (My University, 2019)
Hipokalemik periyodik paralizi, periyodik kas güçsüzlüğü veya paralizi atakları ile karakterize konjenital birhastalıktır. Ataklar, günde veya yılda bir olup birkaç saat veya birkaç gün sürebilir. Atak sırasında serumdaki potasyumseviyesi düşüktür. Ama ataklar arasında serum potasyum seviyesi normaldir. Vücutta potasyum eksikliği yoktur. Bu olgusunumunda, ilk ailesel hipokalemik periyodik paralizi atağını, egzersiz sonrası geçiren ve soyağacı taramasında babası,dedesi ve amcasında benzer yakınmalar saptanan, 16 yaşında bir olgu, klinik ve laboratuvar özellikleri ile sunulmuştur

Hypokalemic periodic paralysis is a congenital disorder which is characterized by intermittent episodes of muscle weakness or paralysis. The attacks can occur everyday or once a year, may last for a few hours or for several days. Serum potassium level is low during the attack. But serum potassium levels are normal between two attacks. There is no potassium deficiency in the whole body. In this report, a 16 years old boy, whose grandfather, father and uncle had the same semptoms, and had his first attack of familial hypokalemic periodic paralysis following a grand exercise were presented according to the clinical and laboratory features.
Familial Hypokalemic Periodic Paralysis - Case Report
Keywords: Genel ve Dahili Tıp